A Prospective Study to Determine the Relationship of the Subjective, Objective and Radiographic Method of Treatment of Adults Who Sustained Fractures of the Shafts of Both Bones of the Forearm - Dr. Manoj Kumar, Dr. Swati Sinha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Aim and objective: The aim of the study was to determine relationship of the subjective, objective and radiographic method of treatment. Material and Methods: A prospective study was conducted in the Department of orthopaedics ESIC Medical College, Bihta, Patna, Bihar, India for the period of 1 year. Three methods of treatment were utilized: open reduction and internal fixation (ORIF), closed reduction and casting (CR), and external skeletal fixation with pins-in-plaster (PIP). The method of treatment was chosen by the attending surgeon based upon his experience and the type of injury. Results: Union occurred in 92 percent of radius fractures and 95 percent of ulna fractures, with an average time to union of 15.4 weeks for the radius and 16.8 weeks for the ulna. Union was more frequent after closed than after open fractures. This difference was most apparent in radius fractures where 13 percent of open fractures developed nonunions, compared to only 3 percent of closed injuries (p = 0.140). Also, the average time to union was 16 percent longer for open than for closed fractures of the radius (p = 0.022), and 35 percent longer for open fractures of the ulna (p = 0.010). Neither the frequency of nor the time to union varied significantly with the method of treatment. The amount of forearm rotation lost was directly proportional to the loss of normal alignment, reaching a mean of 39 degrees when the combined malalignment of the radius and ulna exceeded thirty degrees (p = 0.07). Conclusion: For this series of 120 adult patients, the end results following treatment of fractures of the shafts of the radius and ulna were good to excellent regardless of the method of treatment chosen. Except for a longer time to union and a higher infection rate, the outcomes of open and closed fractures were very similar. The presence of associated injuries was a strong predictor of a compromised end result.